Optimal design of frequency dependent three-layered rectangular composite beams for low mass and high damping. (February 2015) - Hamdaoui, M.; Robin, G.; Jrad, M.; Daya, E.M.
Abstract: Visco-elastic materials are widely used for noise and vibrations damping. They are characterized by a visco-elastic layer sandwiched between two elastic layers. As far as the performances of damping treatments are concerned, the optimal design of sandwich structures has become an important research field. In this work, an optimal design approach for choosing the most suitable material for high damping and low mass for a sandwich beam is investigated. Two frequency dependent visco-elastic materials (PVB and 3M ISD112) are considered. The damping characteristics (eigenfrequencies and damping ratios) of the sandwich beam are determined by solving a non-linear eigenvalue problem. A multi-objective optimization approach based on evolutionary algorithms is used to find the Pareto surface that minimizes the mass and maximizes the damping. The optimization variables are the thicknesses of the visco-elastic and elastic layers. The total beam thickness is kept constant and its maximal deflection under its own weight is limited to its thickness. It is found that the Pareto front for ISD112 material reduces to one point while for the PVB it is composed of several points. It is shown that choosing the most appropriate material for high damping and low weight depends on the importance of each criterion.